Coding interactions in Motivational Interviewing with computer-software: What are the advantages for process researchers? - Klonek, Florian E.; Quera, Vicenç; Kauffeld, Simone (Computers in human behavior, 2015)
[Display omitted] •We present advantages of software support in coding Motivational Interviewing.•The software instrument showed excellent to good interrater reliability.•The software and paper instrument obtained similar results on convergent validity.•Behavior slicing indicated that it is not necessary to code the entire interaction.•We provide three coded demo interactions in two languages for the software version. Motivational Interviewing (MI) is an evidence-based behavior change intervention. The interactional change processes that make MI effective have been increasingly studied using observational coding schemes. We introduce an implementation of a software-supported MI coding scheme—the Motivational Interviewing Treatment Integrity code (MITI)—and discuss advantages for process researchers. Furthermore, we compared reliability of the software version with prior results of the paper version. A sample of 14 double-coded dyadic interactions showed good to excellent interrater reliabilities. We selected a second sample of 22 sessions to obtain convergent validity results of the software version: substantial correlations were obtained between the software instrument and the Rating Scales for the Assessment of Empathic Communication. Finally, we demonstrate how the software version can be used to test whether single code frequencies obtained by using intervals shorter than 20min (i.e., 5 or 10min) are accurate estimates of the respective code frequencies for the entire session (i.e., behavior slicing). Our results revealed that coding only a 10-min interval provides accurate estimates of the entire session. Our study demonstrates that the software implementation of the MITI is a reliable and valid instrument. We discuss advantages of the software version for process research in MI.